2020
DOI: 10.24136/oc.2020.012
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and barriers to cooperation in the process of building a place?s brand: perspective of tourist region stakeholders in Poland

Abstract: Research background: Cooperation within the public and the private sectors is one of the conditions for a tourist region to achieve a competitive advantage, and it is one of the most important aspect for building a regional tourist brand. Research studies often raise the issue of tourism cooperation; however, there are few papers undertaking this topic in the context of place branding. The issue of benefits and barriers of this type of cooperation seen from the perspective of the involved stakeholders is rarel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Engaging stakeholders in managing a touristic area allows for establishing consensus and avoiding conflicts, advancing partnership and increasing responsibility as well as building trust to public institutions [ 49 ], creating and better use of the local human and social capital of touristic areas [ 6 , 86 , 87 ], as well as adds to increased quality of the project [ 55 , 88 ]. Stakeholders participation allows to enhance multilateral influence and interaction between all actors in a given area [ 49 , 27 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engaging stakeholders in managing a touristic area allows for establishing consensus and avoiding conflicts, advancing partnership and increasing responsibility as well as building trust to public institutions [ 49 ], creating and better use of the local human and social capital of touristic areas [ 6 , 86 , 87 ], as well as adds to increased quality of the project [ 55 , 88 ]. Stakeholders participation allows to enhance multilateral influence and interaction between all actors in a given area [ 49 , 27 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…The governance of destinations is becoming an increasingly important research topic [3][4][5]. Recently, the social aspects of governance, such as citizen participation and collaboration among stakeholders, have received increased attention [5,6]. Over the past twenty-five years there has been a growing body of tourism research on stakeholder engagement in successful tourism planning and development [7].…”
Section: Introductionmentioning
confidence: 99%
“…Moutanin Rescue Service works with the public and private sectors to create a safe environment. Such cooperation will improve their position and the ability to communicate better with the public (Kiryluk, et al, 2020). It is also important to expand the number of rescuers performing emergency interventions.…”
Section: Discussionmentioning
confidence: 99%
“…There are benefits and obstacles. Benefits are grouped into categories: economic, organisational, marketing and social; and barriers include economic, organisational, socio-cultural and political determinants (Kiryluk et al, 2020). Moreover, the collaborative approach by mixing the different points of view of stakeholders produces a range of positive outcomes and increases the efficacy of tourism policies (Gori et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research has shown that the role of local governments in tourism development is primary important through collaboration with other stakeholders (Kiryluk et al, 2020;Kismartini & Pujiyono, 2020;Lan & Chau, 2020;Schmidt & Altshuler, 2021;Yasir et al, 2021). Collaboration between multi-stakeholders is widely acknowledged as a critical success factor for resolving sustainability problems in tourism sectors (Foley et al, 2017;Reed, 1999;Waayers et al, 2012), but related to stakeholder collaboration in post-COVID-19 economic recovery, especially in local governments in developing countries, is still very limited.…”
Section: Introductionmentioning
confidence: 99%